2021
DOI: 10.1038/s41538-021-00096-1
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in 3D peptide hydrogel models in cancer research

Abstract: In vitro cell culture models on monolayer surfaces (2D) have been widely adapted for identification of chemopreventive food compounds and food safety evaluation. However, the low correlation between 2D models and in vivo animal models has always been a concern; this gap is mainly caused by the lack of a three-dimensional (3D) extracellular microenvironment. In 2D models, cell behaviors and functionalities are altered, resulting in varied responses to external conditions (i.e., antioxidants) and hence leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 72 publications
(155 reference statements)
0
17
0
Order By: Relevance
“…This would mirror a similar approach to the use of hydrogels in 3D cell culture and the progress of tumour organoids in cancer research only in a microbial cell setting. 152 Peptide hydrogels could be tailored to serve as gel platforms to study the growth and maturation of planktonic bacteria into the biofilm phenotype. Capturing the early stage transition from planktonic to biofilm form would be especially beneficial.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This would mirror a similar approach to the use of hydrogels in 3D cell culture and the progress of tumour organoids in cancer research only in a microbial cell setting. 152 Peptide hydrogels could be tailored to serve as gel platforms to study the growth and maturation of planktonic bacteria into the biofilm phenotype. Capturing the early stage transition from planktonic to biofilm form would be especially beneficial.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…One of the major limitations of these techniques is weak cell-to-cell interactions resulting in spheroids that poorly mimic in vivo 3D TME. 9 , 23 Furthermore, pellet culture lacks throughput and generates 3D spheroids that are vulnerable to shear stress from centrifugation. 19 3D spheroids generated by spinner culture, magnetic levitation, or liquid overlay techniques exhibit significant heterogeneity in both size and shape.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 21 , 24 , 34 36 Recent studies suggest that, in the absence of ECM, 3D spheroids exhibit poorer cell-to-cell communication and are physiologically less relevant compared to spheroids generated in ECM-containing systems. 9 , 23 , 37 The droplet-based approach overcomes this limitation by incorporating different types of soft hydrogel materials that can serve as a scaffold for 3D cell culture. Several studies have demonstrated that a hydrogel scaffold provides mechanical forces for cancer cells to support spheroids possessing strong cell-to-cell interactions, extracellular matrix deposition between cells, and gradients in nutrient concentration from the core to the shell of the spheroid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproduction of in vivo conditions for cell growth in 3D requires a gelatinous and flexible matrix, and BNC has adequate characteristics to serve this purpose. The mechanical strength and flexibility of BNC scaffolds compensate for the most common disadvantages of peptide hydrogel matrices used in current 3D cell culture settings [ 20 , 21 ]. Additionally, the BNC scaffolds represent an easily produced low-cost alternative to expensive peptide hydrogel matrices that remain expensive due to difficulties in their production.…”
Section: Introductionmentioning
confidence: 99%